The Cosmic-Chemical Bond : Chemistry from the Big Bang to Planet Formation - Williams, DA; Hartquist, TW (Milton Road : RSC Publishing, 2013)
Introducing astrochemistry to a wide audience, this book describes how molecules formed in chemical reactions occur in a range of environments in interstellar and circumstellar space.
Keywords: Astronomy -- Specific Celestial Bodies and Phenomena; Cosmic Bond